Entry points for climate-informed planning for the water resources and agriculture sectors in Cambodia - Va Dany (2018)
© 2016, Springer Science+Business Media Dordrecht. Incorporating climate change concerns into national development planning allows adaptation to happen in harmony with the sustainable development of a country. Cambodia has received international support to enable climate change-resilient development; “mainstreaming climate change” is one of the key recent strategies. This article aims to identify entry points for integrating climate change concerns into national development planning, especially for the wate r resources and agriculture sectors. The study uses institutional ethnography research methods with informants drawn from government organisations, local academic institutions, and development partners, together with content analysis of key policy documents. It was found that the Cambodian national planning process restricts the involvement of other actors such as researchers, civil society, and private sector; yet flexible, in that it provides opportunities for the inclusion of climate change and other related concerns. The study identified specific entry points in key policy documents, such as the National Strategic Development Plans, and ministries’ plans. Other entry points were identified in the development planning process, for example, in the process of development departments and ministries’ plans, and actors such as department planners, and departments of planning of line ministries. Climate-informed planning is now plausible; more significant integration of concerns with future climate change, however, will require more commitment and stronger connections among national planning stakeholders, adaptation actors, and research communities.